2014
DOI: 10.1016/j.bbi.2014.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Measures of adiposity predict interleukin-6 responses to repeated psychosocial stress

Abstract: Objective Overweight and obese individuals, who comprise approximately two-thirds of the U.S. population, are at increased risk for developing a range of diseases. This increased risk may be due in part to maladaptive stress responses within this group, including heightened low-grade inflammation and HPA axis non-habituation. In this study we tested the relationship between adiposity, plasma interleukin-6 (IL-6) and HPA axis responses to repeated stress. Methods Sixty-seven healthy participants were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 50 publications
4
56
0
2
Order By: Relevance
“…Consistent with most previous reports, baseline IL-6 levels were associated with older age, greater adiposity levels, and higher depressive symptoms score and inversely with socioeconomic position and frequency of physical activity [9,10,13]. We observed an increase (31 %) in circulating levels of IL-6 in response Values are means (SD) or N (%)…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with most previous reports, baseline IL-6 levels were associated with older age, greater adiposity levels, and higher depressive symptoms score and inversely with socioeconomic position and frequency of physical activity [9,10,13]. We observed an increase (31 %) in circulating levels of IL-6 in response Values are means (SD) or N (%)…”
Section: Discussionsupporting
confidence: 90%
“…An adiposity component was computed using participants' BMI, waist circumference, and fat mass [10,13]. Mood symptoms were assessed with the Center for Epidemiologic Study Depression (CES-D) Scale [25], and scores were dichotomized into <16 or ≥16 (no/little risk and at risk for depression) [26].…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been stated that the three pro-inflammatory cytokines, IL-6, TNF and IL-1β are implicated in the pathophysiology of depressive illness (21). IL-6 has been proposed to be central in the systemic consequences of psychological stress, mediating with stress through the hypothalamic-pituitary-adrenal (HPA) axis and catecholamines leading to insulin resistance, coagulation abnormalities and endothelial dysfunction (22)(23)(24). Similarly, depression has been associated with systemic diseases involving induction of a pro-inflammatory state or upregulation of inflammatory markers.…”
Section: Central and Peripheral Markers Of Inflammation In Depressionmentioning
confidence: 99%
“…Prentice [21] suggested that eating after stress can worsen health status, particularly in individuals with dysfunctional eating patterns. McInnis et al [22] explained obesity in terms of cellular disturbances. Maladaptive stress triggers a compensatory mechanism that could explain obesity and overweight.…”
Section: Introductionmentioning
confidence: 99%